Characterization of Membrane Patch‐Ion Channel Probes for Scanning Ion Conductance Microscopy. Issue 18 (11th December 2017) - Shi, Wenqing; Zeng, Yuhan; Zhu, Cheng; Xiao, Yucheng; Cummins, Theodore R.; Hou, Jianghui; Baker, Lane A.
Abstract: Integration of dual‐barrel membrane patch‐ion channel probes (MP‐ICPs) to scanning ion conductance microscopy (SICM) holds promise of providing a revolutionized approach of spatially resolved chemical sensing. A series of experiments are performed to further the understanding of the system and to answer some fundamental questions, in preparation for future developments of this approach. First, MP‐ICPs are constructed that contain different types of ion channels including transient receptor potential vanilloid 1 and large conductance Ca2 + ‐activated K + channels to establish the generalizability of the methods. Next, the capability of the MP‐ICP platforms in single ion channel activity measurements is proved. In addition, the interplay between the SICM barrel and the ICP barrel is studied. For ion channels gated by uncharged ligands, channel activity at the ICP barrel is unaffected by the SICM barrel potential; whereas for ion channels that are gated by charged ligands, enhanced channel activity can be obtained by biasing the SICM barrel at potentials with opposite polarity to the charge of the ligand molecules. Finally, a proof‐of‐principle experiment is performed and site‐specific molecular/ionic flux sensing is demonstrated at single‐ion‐channel level, which show that the MP‐ICP platform can be used to quantify local molecular/ionic concentrations. Abstract : Measuring minute concentrations of molecules and ions – in particular at biological interfaces at the single‐cell level – is of great significance in modern bioanalytical chemistry. Integration of ion channels into pipette probes and further integration with scanning ion conductance microscopy provide a revolutionary approach for spatially‐resolved chemical sensing, opening up exciting future opportunities to elucidate underlying mechanisms of cellular communication processes.